Degrowth between normativism and reality - Aljaž Kunčič; Marjan Svetličič (Stanovništvo)
This article addresses the increasing debates over the limitations of high-growth models that have contributed to environmental degradation and polycrises. Based on a comprehensive literature review, we look into the basic characteristics and differences between the alternative degrowth and similar new development models; examine the paradigm through the lens of its critics; and look into its viability. The analysis highlights that while degrowth presents a theoretically compelling alternative to traditional growth models, it faces significant practical challenges in implementation, particularly due to its reliance on deep systemic changes and shifts in public values. In the empirical section, we test the hypothesis that countries with better sustainable development progress are more successful than those prioritizing economic outcomes. To do this, we show graphically and analyze the correlation between the average GDP growth and changes in the sustainable development measure using Pearson’s correlation coefficient. We rank countries based on their sustainable development and economic performance, averaging these rankings to identify potential degrowth leaders over the past 20 years. Our findings indicate that, while theoretically appealing, the degrowth model faces significant challenges in practice, with no statistical evidence supporting a negative correlation between degrowth and sustainable development progress.